INCREASED TOLERANCE OF TRIFOLIATE ORANGE (PONCIRUS TRIFOLIATA) SEEDLINGS TO WATERLOGGING AFTER INOCULATION WITH ARBUSCULAR MYCORRHIZAL FUNGI - Y. N. Zou; A. K. Srivastava; Q. S. Wu; Y. M. Huang (Journal of Animal and Plant Sciences, 2014)
Growth suppressive role of waterlogging (WL) as an important abiotic stress to perennial plants is well known. A pot experiment was conducted to study a potential contribution of arbuscular mycorrhizal fungi (AMF, Diversispora spurca) on WL tolerance of trifoliate orange (Poncirustrifoliata L. Raf.) seedlings on the basis of growth, root system architecture, and antioxidant enzymes. Four-month-old seedlings inoculated with or without D. spurca were subjected to WL with non-waterlogging (NWL) as control treatment. Root mycorrhizal (MY) colonization and vesicles notably decreased, but entry points significantly increased after 36 days of WL. The WL restricted plant growth performance and numbers of different order lateral roots, but the MY symbiosis exhibited theameliorating roles on plant growth, root morphology (total length, surface area, projected area, and volume) and numbers of different order lateral roots. The AMF inoculation significantly increased superoxide dismutase and catalase activities in leaf and root under both NWL and WL, thereby, resulting in lower oxidative damage in terms of malondialdehide concentration. These results suggest that the MY seedlings were biochemically and morphologically better prepared to tolerate WL compared to the NMY seedlings.
Keywords: Antioxidant enzymes; Arbuscular mycorrhiza; Root system architecture; Trifoliate orange; Waterlogging